1990
DOI: 10.1083/jcb.111.6.3013
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of microtubule dynamics and nucleation during polarization in MDCK II cells.

Abstract: Abstract. MDCK cells form a polarized epithelium when they reach confluence in tissue culture. We have previously shown that concomitantly with the establishment of intercellular junctions, centrioles separate and microtubules lose their radial organization (Bacallao, R., C. Antony, C. Dotti, E. Karsenti, E. H. K. Stelzer, and K. Simons. 1989. J. Cell Biol. 109:2817-2832. Buendia, B., M. H. Brt, G. Griffiths, and E. Karsenti. 1990Karsenti. . 110:1123Karsenti. -1136. In this work, we have examined the patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(39 citation statements)
references
References 34 publications
(41 reference statements)
2
37
0
Order By: Relevance
“…8a) 15 . Given that MTs in polarized epithelial cells are stabilized compared with less differentiated cells 20,21 , these results further suggest that the N-terminal region may not require the KR-rich region to function in epithelial cells. Recently, the MT minusend-binding proteins, CAMSAPs, have been reported to exert a strong stabilizing effect on non-centrosomal MTs in epithelial cells [22][23][24] .…”
Section: Discussionmentioning
confidence: 81%
“…8a) 15 . Given that MTs in polarized epithelial cells are stabilized compared with less differentiated cells 20,21 , these results further suggest that the N-terminal region may not require the KR-rich region to function in epithelial cells. Recently, the MT minusend-binding proteins, CAMSAPs, have been reported to exert a strong stabilizing effect on non-centrosomal MTs in epithelial cells [22][23][24] .…”
Section: Discussionmentioning
confidence: 81%
“…Due to its preference for" + ---+ -" transport, it may be involved in trichocyst docking. Remarkably, such"+ ---+ -" directed transport to the cell periphery, as established for trichocysts (Plattner et al, 1982;Glas-Albrecht et al, 1991), has also been found in epithelia (Bacallao et al, 1989;Bre et al, 1990). Table I summarizes the relevant molecular details known so far from Paramecium.…”
Section: Microtubules As Long-range Signals For Vesicle Traffickingmentioning
confidence: 80%
“…By contrast, in many other epithelial cells most MTs are noncentrosomal and align along the apicobasal polarity axis. They create asymmetry by orienting their minus-and plus-ends towards the apical and basal membrane domains, respectively (Bacallao et al, 1989;Bre et al, 1990).…”
Section: Assembly Of the Junctional Beltmentioning
confidence: 99%